Evaluation of Paederia foetida L. Extract on Liver Weight Alterations in an Escherichia coli Sepsis Mouse Model - Savitri, Lisa; Elfred Rinaldo Kasimo; Rochmad Krissanjaya (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2025)
Sepsis is a critical medical condition caused by a systemic immune response to infection and is often associated with severe organ dysfunction and high mortality. Bacterial sepsis, including cases triggered by Escherichia coli, can damage host tissues as the immune response becomes dysregulated. Infections involving E. coli in the digestive tract have become increasingly common. Among the affected organs, the liver plays a key role in metabolic regulation and host defense during sepsis. This study investigated the effect of Paederia foetida L. leaf extract on liver weight in a murine sepsis model. Introducing E. coli induces systemic infection and establishes the sepsis model, a commonly used approach in experimental studies to mimic the clinical features of sepsis. After acclimation, mice received treatments for 14 days across several groups: a normal control (N), a negative control (K–) given distilled water, a positive control (K+) given ciprofloxacin, and three treatment groups receiving P. foetida extract at 100 mg/kg BW (P1), 300 mg/kg BW (P2), and 500 mg/kg BW (P3). The analysis revealed significant differences among groups, with the highest mean liver weight recorded in P1 (1.3750 ± 0.3932). Liver abnormalities included enlargement, increased organ mass, swelling, and thickening of one liver lobe, which may reflect heightened hepatic workload during infection and toxin clearance. Interestingly, the normal group showed greater liver weight than several treatment groups, possibly due to fatty accumulation within hepatic tissue, which can influence overall organ mass.